Pengelolaan Air Permukaan di Wonoharjo Kabupaten Karanganyar - Supadi Supadi (KEAIRAN, 2005)
The purpose of the research is to discuss and choose of the structures for managing of run-of water resources.This research is conducted by observing the soil layers of 130x300 m2 wide and 4 m depth at 17th stations in Kabupaten Karang Anyar. Water table, hard soil, and gravel-soil is parameter for choosing the structure that is allowable. Hard-soil or water tabel on 2.0 - 2.5 meter at Colomadu, Kebakramat, Jaten, Tasik Madu,and Karang Anyar. Hard-soil or water tabel on 2.5 – 3.0 meter at Matesih, Karang Pandan, Mojogedang, Jumapolo, and Ngargoyoso.Hard-soil on 3.0 – 4.0 at Kerjo, Jumantono, Jatipuro, and Jatiyoso. Big gravel-soil at Tawang Mangu, and Jenawi.The result showed that small dam or horizontal infiltration hole-water is allowable at Jenawi, Tawang Mangu, Karang Anyar, Jaten, Tasik Madu. Vertical infiltration hole-water is allowable at anothers. Keywords: small dam, infitration hole-water, hard soil, water table, big gravel-soilPermalink: http://ejournal.undip.ac.id/index.php/keairan/article/view/2746[How to cite: Supadi (2005). Pengelolaan Air Permukaan di Wonoharjo Kabupaten Karanganyar, Jurnal Keairan, 12 (2): 64-71]